PEMBATALAN MEREK DITINJAU DARI UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS (STUDI KASUS PUTUSAN KASASI NOMOR 375 K/PDT.SUS.HKI/2020) - Naim, Putri; Ismi, Hayatul; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The era of global trade can be maintained if there is a healthy business competition climate. Currently, more and more entrepreneurs are competing in producing their respective products, both middle and upper-middle entrepreneurs. Entrepreneurs produce the best possible products because they can see that most Indonesians prefer good and guaranteed quality. In terms of food needs, people usually choose products according to their tastes, for reasons of health and guaranteed taste. To distinguish one product from another, it can be distinguished by the presence of a brand. The purpose of writing this thesis: First, to find out the cancellation of the trademark regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications. Second, to find out the reasons for the judge in canceling the "Eiger" trademark of Budiman Tjoh (Case Study Number 375). K/Pdt.Sus.HKI/2020). The author conducts research with the Normative Method or what is known as legal research. Normative legal research is to find the truth of coherence. From the results of the study, there are two main things that can be key: First, the cancellation of the mark regulated in Number 20 of 2016 concerning Marks and Geographical Indications, secondly, the reasons for the judge to cancel the "Eiger" trademark of Budiman Tjoh (Case Study Number 375 K/ Pdt.Sus.HKI/2020) The author's suggestions, in this research, are: According to the author, the trademark cancellation lawsuit in the cassation case study number 375K/Pdt.Sus.HKI/2020 is seen and investigated again whether the case is in accordance with the law that should apply to the case. And judges should, in making a decision, have to look at similar cases, how similar cases are handled, how the decision is made which will be taken into consideration by the judge to decide the same case.Keywords: Brand – Brand Rights –Eiger